Translation-dependent retrograde signaling coordinates high-light acclimation in plants - Marten Moore; Aaron B. Smith; Melanie Wegener; Pravin B. Khambalkar; Rebeccah V. Tyrrell; Brea C. Watts; Samuel J. Nix; Hong Ting Tsang; Muhammad Ansar Farooq; Diep R. Ganguly; Robert T. Furbank; Maria Ermakova; et al. (Molecular Plant, 2026)

Characterization of brain lesions in Danish farm mink (Neogale vison) with acute, fatal SARS-CoV-2 infection - Michelle L. Quaade; Karen M. Wegener; Louise W.D. Otzen; Thomas B. Rasmussen; Anne S.V. Hammer (Journal of Comparative Pathology, 2025)

Blood Oxygenation Level–Dependent Cerebrovascular Reactivity–Derived Steal Phenomenon May Indicate Tissue Reperfusion Failure After Successful Endovascular Thrombectomy - Jacopo Bellomo; Martina Sebök; Vittorio Stumpo; Christiaan H. B. van Niftrik; Darja Meisterhans; Marco Piccirelli; Lars Michels; Beno Reolon; Giuseppe Esposito; Tilman Schubert; Zsolt Kulcsar; Andreas R. Luft; et al. (Translational Stroke Research, 2025)
In acute ischemic stroke due to large-vessel occlusion (LVO), the clinical outcome after endovascular thrombectomy (EVT) is influenced by the extent of autoregulatory hemodynamic impairment, which can be derived from blood oxygenation level–dependent cerebrovascular reactivity (BOLD-CVR). BOLD-CVR imaging identifies brain areas influenced by hemodynamic steal. We sought to investigate the presence of steal phenomenon and its relationship to DWI lesions and clinical deficit in the acute phase of ischemic stroke following successful vessel recanalization. From the prospective longitudinal IMPreST (Interplay of Microcirculation and Plasticity after ischemic Stroke) cohort study, patients with acute ischemic unilateral LVO stroke of the anterior circulation with successful endovascular thrombectomy (EVT; mTICI scale ≥ 2b) and subsequent BOLD-CVR examination were included for this analysis. We analyzed the spatial correlation between brain areas exhibiting BOLD-CVR-associated steal phenomenon and DWI infarct lesion as well as the relationship between steal phenomenon and NIHSS score at hospital discharge. Included patients ( n = 21) exhibited steal phenomenon to different extents, whereas there was only a partial spatial overlap with the DWI lesion (median 19%; IQR, 8–59). The volume of steal phenomenon outside the DWI lesion showed a positive correlation with overall DWI lesion volume and was a significant predictor for the NIHSS score at hospital discharge. Patients with acute ischemic unilateral LVO stroke exhibited hemodynamic steal identified by BOLD-CVR after successful EVT. Steal volume was associated with DWI infarct lesion size and with poor clinical outcome at hospital discharge. BOLD-CVR may further aid in better understanding persisting hemodynamic impairment following reperfusion therapy.

Citizen science’s transformative impact on science, citizen empowerment and socio-political processes - Julia von Gönner; Thora M. Herrmann; Till Bruckermann; Michael Eichinger; Susanne Hecker; Friederike Klan; Julia Lorke; Anett Richter; Ulrike Sturm; Silke Voigt-Heucke; Wiebke Brink; Christin Liedtke; et al. (Socio-Ecological Practice Research, 2023)
Citizen science (CS) can foster transformative impact for science, citizen empowerment and socio-political processes. To unleash this impact, a clearer understanding of its current status and challenges for its development is needed. Using quantitative indicators developed in a collaborative stakeholder process, our study provides a comprehensive overview of the current status of CS in Germany, Austria and Switzerland. Our online survey with 340 responses focused on CS impact through (1) scientific practices, (2) participant learning and empowerment, and (3) socio-political processes. With regard to scientific impact, we found that data quality control is an established component of CS practice, while publication of CS data and results has not yet been achieved by all project coordinators (55%). Key benefits for citizen scientists were the experience of collective impact (“making a difference together with others”) as well as gaining new knowledge. For the citizen scientists’ learning outcomes, different forms of social learning, such as systematic feedback or personal mentoring, were essential. While the majority of respondents attributed an important value to CS for decision-making, only few were confident that CS data were indeed utilized as evidence by decision-makers. Based on these results, we recommend (1) that project coordinators and researchers strengthen scientific impact by fostering data management and publications, (2) that project coordinators and citizen scientists enhance participant impact by promoting social learning opportunities and (3) that project initiators and CS networks foster socio-political impact through early engagement with decision-makers and alignment with ongoing policy processes. In this way, CS can evolve its transformative impact.

An incipient invasion of brown anole lizards (Anolis sagrei) into their own native range in the Cayman Islands: a case of cryptic back-introduction - Jason J. Kolbe; Johanna E. Wegener; Yoel E. Stuart; Ushuaia Milstead; Katherine E. Boronow; Alexis S. Harrison; Jonathan B. Losos (Biological Invasions, 2017)

Neonatal domoic acid alters in vivo binding of [11C]yohimbine to α2-adrenoceptors in adult rat brain - Majken B. Thomsen; Thea P. Lillethorup; Steen Jakobsen; Erik H. Nielsen; Mette Simonsen; Gregers Wegener; Anne M. Landau; R. Andrew Tasker (Psychopharmacology, 2016)

Chronic treatment with the phosphodiesterase type 5 inhibitors sildenafil and tadalafil display anxiolytic effects in Flinders Sensitive Line rats - Nico Liebenberg; Brian H. Harvey; Linda Brand; Gregers Wegener; Christiaan B. Brink (Metabolic Brain Disease, 2012)

[11C]Mirtazapine binding in depressed antidepressant nonresponders studied by PET neuroimaging - Donald F. Smith; Bo S. Stork; Gregers Wegener; Mahmoud Ashkanian; Steen Jakobsen; Dirk Bender; Hélène Audrain; Karina H. Vase; Søren B. Hansen; Poul Videbech; Raben Rosenberg (Psychopharmacology, 2009)

Receptor occupancy of mirtazapine determined by PET in healthy volunteers - Donald F. Smith; Bo S. Stork; Gregers Wegener; Steen Jakobsen; Dirk Bender; Hélène Audrain; Svend B. Jensen; Søren B. Hansen; Anders Rodell; Raben Rosenberg (Psychopharmacology, 2007)

The extrinsic proteins of Photosystem II - Johnna L. Roose; Kimberly M. Wegener; Himadri B. Pakrasi (Photosynthesis Research, 2007)

Soft-rot Resistance of Coloured Potato Cultivars (Solanum tuberosum L.): The Role of Anthocyanins - Christina B. Wegener; Gisela Jansen (Potato Research, 2007)

Inheritance of a pectate lyase mediated soft rot resistance in crosses between transgenic potato lines of cv. désirée andS. tuberosum cultivars - Christina B. Wegener (Potato Research, 2003)

Transgenic potatoes expressing anErwinia pectate lyase gene — results of a 4-year field experiment - C. B. Wegener (Potato Research, 2001)

Toxicological and ecotoxicological assessment of water tracers - H. Behrens; U. Beims; H. Dieter; G. Dietze; T. Eikmann; T. Grummt; H. Hanisch; H. Henseling; W. Käß; H. Kerndorff; C. Leibundgut; U. Müller-Wegener; et al. (Hydrogeology Journal, 2001)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)